Human ABC transporter ABCG2/BCRP expression in chemoresistance: basic and clinical perspectives for molecular cancer therapeutics - Noguchi K; Katayama K; Sugimoto Y (Dove Medical Press, 2014)
Kohji Noguchi, Kazuhiro Katayama, Yoshikazu Sugimoto Division of Chemotherapy, Faculty of Pharmacy, Keio University, Tokyo, Japan Abstract: Adenine triphosphate (ATP)-binding cassette (ABC) transporter proteins, such as ABCB1/P-glycoprotein (P-gp) and ABCG2/breast cancer resistance protein (BCRP), transport various structurally unrelated compounds out of cells. ABCG2/BCRP is referred to as a “half-type” ABC transporter, functioning as a homodimer, and transports anticancer agents such as irinotecan, 7-ethyl-10-hydroxycamptothecin (SN-38), gefitinib, imatinib, methotrexate, and mitoxantrone from cells. The expression of ABCG2/BCRP can confer a multidrug-resistant phenotype on cancer cells and affect drug absorption, distribution, metabolism, and excretion in normal tissues, thus modulating the in vivo efficacy of chemotherapeutic agents. Clarification of the substrate preferences and structural relationships of ABCG2/BCRP is essential for our understanding of the molecular mechanisms underlying its effects in vivo during chemotherapy. Its single-nucleotide polymorphisms are also involved in determining the efficacy of chemotherapeutics, and those that reduce the functional activity of ABCG2/BCRP might be associated with unexpected adverse effects from normal doses of anticancer drugs that are ABCG2/BCRP substrates. Importantly, many recently developed molecular-targeted cancer drugs, such as the tyrosine kinase inhisbitors, imatinib mesylate, gefitinib, and others, can also interact with ABCG2/BCRP. Both functional single-nucleotide polymorphisms and inhibitory agents of ABCG2/BCRP modulate the in vivo pharmacokinetics and pharmacodynamics of these molecular cancer treatments, so the pharmacogenetics of ABCG2/BCRP is an important consideration in the application of molecular-targeted chemotherapies. Keywords: kinase inhibitor, SNP, single-nucleotide polymorphisms, molecular target